1987
DOI: 10.1300/j082v13n04_04
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Gay and Lesbian Teachers

Abstract: This study summarized a survey of 97 homosexual individuals who were currently teaching or who had been teachers. The focus of the survey was to gain insight into the experiences of such individuals in the public schools. It was found that 25% of the respondents had left teaching; a little more than half of this group left at least partially because of their sexual preference. About 82% were out of the closet to at least one person while teaching; nearly half of those who were "out" had chosen another teacher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…For example, jobs that involved contact with young people, particularly K-12 and preschool children, were long identified as particularly problematic for both gay men and lesbians (Olson, 1987). Even in U.S. states that did not explicitly ban sexual minorities from teaching in the public schools, gay and lesbian educators indicated that they felt threatened by stereotypes that associated gay men, and to a lesser extent lesbians, with sexual molestation.…”
Section: How Does Discrimination Against Sexual Minorities Operate Atmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, jobs that involved contact with young people, particularly K-12 and preschool children, were long identified as particularly problematic for both gay men and lesbians (Olson, 1987). Even in U.S. states that did not explicitly ban sexual minorities from teaching in the public schools, gay and lesbian educators indicated that they felt threatened by stereotypes that associated gay men, and to a lesser extent lesbians, with sexual molestation.…”
Section: How Does Discrimination Against Sexual Minorities Operate Atmentioning
confidence: 99%
“…Others anticipated moral panic from parents and others about "recruiting" young people into the gay subculture (Burgoon et al, 1989;Ferfolja, 2009;Griffin, 1991;Harbeck, 1991;Kissen, 1996;Olson, 1987). One consequence was particularly high rates of concealment among gay and lesbian K-12 teachers, and continuing underrepresentation in the field as a whole (Baumle, Compton, & Poston, 2009, p. 164).…”
Section: How Does Discrimination Against Sexual Minorities Operate Atmentioning
confidence: 99%
“…Of even greater concern, disclosing one's sexual orientation may translate into job and housing discrimination (Ragins & Cornwell, 2001). Although specific statistics have been difficult to gather, mounting evidence suggest that gays and lesbians suffer employment discrimination (Jennings, 1994;Olson, 1987;Weaver v Nebo School District, 1998). A similar pattern has been found for people with mental illness.…”
Section: Benefits and Costs To Disclosingmentioning
confidence: 99%
“…Many past studies indicate that sexual minorities experience all forms of discrimination including termination, harassment, violence and loss of career opportunities (Driscoll et al 1996;Hall 1986;Levin 1984;Olson 1987). As stated above, some organizations are gay-friendlier than others, and, as a result, gays and lesbians suffer different degrees of discrimination in the workplace (Pichler 2007).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…First, the decision to limit the scope of the research to gay men was based on the lack of research on the career issues faced this minority group (Croteau 1996;Lonborg and Phillips 1996). Most of the research examining the relationship between sexual identity and career development focuses on lesbians (Boatwright et al 1996;Driscoll et al 1996;Hall 1986;Olson 1987). The primary reason underpinning this research focus is the belief that lesbians face various issues in their career: exploring sexuality, intimate relationships, social networks and changing family relationships (Fassinger 1995).…”
mentioning
confidence: 99%